Students’ Perceptions of Internet Network Problems Facilities at A Public University Using a Qualitative Descriptive Method for Service Improvement - Raden Rocky Anderson; Zidni Ma’ruf; Resa Kurni Pratama; Fattar Firansyah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
This study examines students’ perceptions of internet network services used to support academic activities in higher education. The research was motivated by several issues frequently experienced by students, including unstable internet connections, limited coverage in certain campus areas, network congestion during peak usage periods, repeated login requirements, and limited information regarding technical support services. The objective of this study is to identify students’ perceptions regarding the quality, accessibility, and reliability of campus internet services and to formulate recommendations for service improvement. A qualitative descriptive method was employed through semi structured interviews involving six Electrical Engineering students. The collected data were analyzed using thematic analysis to identify recurring experiences and issues encountered by students. The findings indicate that campus internet services play an important role in supporting access to learning materials, e learning platforms, assignment completion, and other academic activities. However, students reported several challenges related to connection stability, internet speed, roaming capability, and technical support availability. As a practical solution, this study recommends improving network infrastructure, optimizing bandwidth capacity, enhancing roaming functionality across campus areas, and providing clearer technical support information for users. The study provides valuable insights for improving campus internet services and supporting technology-based learning environments more effectively.